Whole-Person, Urobiome-Centric Therapy for Uncomplicated Urinary Tract Infection - Luciano Garofalo; Claudia Nakama; Douglas Hanes; Heather Zwickey (MDPI AG, 2022)
A healthy urinary tract contains a variety of microbes resulting in a diverse urobiome. Urobiome dysbiosis, defined as an imbalance in the microbial composition in the microenvironments along the urinary tract, is found in women with uncomplicated urinary tract infection (UTI). Historically, antibiotics have been used to address UTI. An alternative approach to uncomplicated UTI is warranted as the current paradigm fails to take urobiome dysbiosis into account and contributes to the communal problem of resistance. A whole-person, multi-modal approach that addresses vaginal and urinary tract dysbiosis may be more effective in reducing recurrent UTI. In this review, we discuss strategies that include reducing pathogenic bacteria while supporting commensal urogenital bacteria, encouraging diuresis, maintaining optimal pH levels, and reducing inflammation. Strategies for future research are suggested.